Acquired Strabismus in Linear Scleroderma of the Face - Giorgia Martini; Maria Elisabetta Zannin; Fiorella Rodeghiero; Sandro Dal Pos; Francesco Zulian (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)